Chinese EFL learners’ enjoyment and anxiety in an online class: An idiodynamic approach - Liu, Linlin; Lee, Ju Seong (Studies in Second Language Learning and Teaching, 2025)
While students often experience fluctuations in their positive and negative L2 emotions during online classes, there is a dearth of research on these emotional changes. This study fills this gap by exploring the dynamic nature of enjoyment and anxiety in an online English as a foreign language (EFL) classroom using an idiodynamic method. Seven Chinese EFL university students participated in a series of four online class sessions, each lasting 20 minutes. Following each session, they reviewed video recordings of their performance and rated their enjoyment and anxiety on a minute-by-minute basis. Stimulated recalls, interviews, and field notes identified factors influencing these emotional fluctuations. Results show that, in some cases, both emotions operated in a seesaw relationship, with one rising and the other falling, while in others they operated independently. A closer look reveals that the relationship between these emotions was complex and dynamic, shaped by both internal (e.g., personality) and external (e.g., task difficulty) factors. The findings also show that while EFL students initially experienced emotional turbulence at the beginning of online classes, effective emotional, pedagogical, and technological support from teachers helped learners maintain optimal emotional states over time.